Positive response to trastuzumab deruxtecan in a patient with HER2-mutant NSCLC after multiple lines therapy, including T-DM1: a case report - Xu, Junzhu; He, Bo; Wang, Yunan; Wu, Mengjia; Lu, Yanyi; Su, Zixuan; Liu, Shujun; Yin, Fengmin; Zhou, Jian-Guo; Hu, Wei (Frontiers in Oncology, 2024)
Lung cancer is the most common cause of cancer-related deaths worldwide[1]. Non-small cell lung cancer (NSCLC) is the predominant form of lung cancer and accounts for 85% of all cases. However, human epidermal growth factor 2 (HER2, erbB-2/neu) mutations occur in only 2–4% of NSCLC patients, more commonly in females, never-smokers, and adenocarcinomas [2]. HER2 is a member of the ErbB receptor tyrosine kinase family, and its mutation in NSCLC is predominantly an in-frame insertion of exon 20 into the tyrosine kinase structural domain, including Y772_A775dupYVMA, G778_P780dup, and G776delinsVC (G776delinsLC)[3, 4], which has a poor overall survival (OS) of only 18–21 months[5]. Although HER2 can be regarded as a therapeutic target, the efficacy of target therapy in HER2-mutated NSCLC has been disputed. Therefore, the standard first-line treatment remains a reference for advanced “driverless” NSCLC. Antibody-drug conjugates (ADCs) are novel antitumor drugs that combine the high specificity of antibody targeting with potent cytotoxic drugs[6]. For cancer patients with HER2 mutation or amplification, particularly breast and gastric cancers, numerous clinical trials have demonstrated the promise of ADCs as an effective treatment strategy. Nevertheless, the research on potentially effective treatments for advanced NSCLC with HER2 mutations are still ongoing. Herein, we present a patient achieving the overall survival (OS) of 46.5 months, who underwent chemotherapy, immune checkpoint inhibitors (ICIs), anti-angiogenesis agents (bevacizumab and anlotinib), pan-HER tyrosine kinase inhibitors (afatinib, pyrotinib, and poziotinib), and ADCs (ado-trastuzumab emtansine [T-DM1], trastuzumab deruxtecan [T-DXd]), and attempt to provide new clues for the effective treatment of patients with HER2-mutated.